MENINGKATKAN PENDIDIKAN KARAKTER ANAK SEJAK DINI DI DESA BUKIT HATARAN TAHUN 2023 - Binsar Tison Gultom; Putri Enzelina Purba; Astri Mahyuni Br Malau; Windriana Lestari Marpaung; Joice Elisa Siadari; Mila Kamelia Simanjuntak (Abdi Jurnal Publikasi, 2023)
Community Service Activities (PkM) carried out by the HKBP Nommensen University FKIP team as part of the Tri Dharma of Higher Education were carried out simultaneously from 06 to 25 February 2023. One of the locations is Hataran Hill, Manik Hataran Village, Sidamanik sub-district , Simalungun district with the aim of the activity is to improve good character education for children from an early age. Based on the results of observations before this activity was carried out, the results obtained in children's character education were still not effective, especially in terms of respecting others, speaking kind words, and maintaining a healthy lifestyle. Departing from the results of these observations, PkM participants together with Field Supervisors (DPL), seek to improve children's character education through GPPK (Character Education Strengthening Movement) activities. this movement consisting of strengthening Religious, Nationalist, Integrity, Independence and Gotong Royong for children in Bukit Hataran hamlet, Manik Hataran. The type of activity carried out by the team is teaching children to always pray before eating, before going to bed and studying. And directing children to always implement MTT (Sorry, Please, and Thank You). In addition, the PkM team also conducts counseling on clean and healthy living behaviors for children, namely by implementing proper and proper hand washing, and maintaining a healthy lifestyle. Based on the analysis of the data, it was found that, increasing knowledge of a child's character in behaving like; manners, discipline, mutual respect, mutual respect for one another, and the more firm belief in their beliefs, the more independent and self-confident as well as increasing healthy living behavior according to what has been taught for three full weeks.